Assessing the effectiveness of digital marketing for Halal tourism using EPIC model at Pesarean Syaikhona Kholil, Bangkalan - Faraby, Muhammad Ersya; Syarif, Muhammad; Aguilika, Deykha; Musadad, Ahmad; Pujiati, Tri; Misno , Misno; Mohammad Ibraheem, Mohammad Jazeel (Universitas Islam Indonesia, 2026)
IntroductionHalal tourism offers a range of travel packages designed to accommodate Muslim travelers. Several components support the development of halal tourism, including halal food, halal transportation, halal hotels, halal logistics, halal financial systems, and halal tour packages that comply with sharī‘ah standards. The main problem addressed in this study is the suboptimal use of digital marketing systems as promotional media for halal tourism in Bangkalan, Madura.ObjectivesThis study aims to identify the digital marketing systems employed by the religious tourism destination Pesarean Syaikhona Kholil Bangkalan as a halal tourism site in Indonesia. In addition, the study tries to assess the effectiveness of digital marketing through social media as part of the promotional strategy for this religious destination.MethodThis research adopts a mixed-methods approach. The qualitative component is used to explain the forms of digital marketing implemented by Pesarean Syaikhona Kholil. Meanwhile, the quantitative component is employed to obtain an assessment of the effectiveness of the destination’s digital marketing initiatives. The qualitative analysis uses the EPIC Model (Empathy, Persuasion, Impact, and Communication).ResultsThe findings reveal that the management of Pesarean Syaikhona Kholil Bangkalan has not fully optimized digital marketing practices, resulting in relatively low visitor numbers. Based on the EPIC Model assessment, the average EPIC rate score is 3.955556, in the “effective” category. This indicates that utilizing digital media as a marketing strategy is effective for tourism promotion.ImplicationsThe results provide implications for the application of digital marketing in promoting Pesarean Syaikhona Kholil as one of Indonesia’s halal tourism destinations. There is a need to strengthen digitalization efforts by leveraging social media platforms such as Instagram, TikTok, Facebook, and WhatsApp to reduce conventional promotional costs and expand market reach. Additionally, synergy between the Bangkalan local government, tourism managers, and the surrounding community is crucial to building a shared vision in supporting the development of Pesarean Syaikhona Kholil Bangkalan as a national halal tourism destination.Originality/NoveltyThis study offers new insights into the use of digital marketing as a promotional tool for halal tourism in Bangkalan. The findings contribute to the development of innovative digital marketing strategies aimed at expanding the market reach of halal tourism in Indonesia. Furthermore, the EPIC Model assessment derived from respondents provides a valuable analytical tool for measuring the effectiveness of digital marketing implemented by tourism managers.